2016
DOI: 10.1111/jrh.12201
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Implementation Strategies to Adapt and Implement a Veteran Peer Coaching Intervention to Improve Mental Health Treatment Engagement Among Rural Veterans

Abstract: As the VA moves to cultivate community partnerships in order to personalize and expand access to care for rural veterans, pre-implementation processes with engaged stakeholders, such as those described here, can help guide other researchers and clinicians to achieve proactive and veteran-centered health care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…With a typically shorter turnaround time, qualitative researchers in implementation science have turned toward rapid analysis techniques in which key concepts are identified in advance to structure and focus the inquiry (32, 39). In the rapid analytic approach used by Hamilton (39), main topics (domains) are drawn from interview and focus group guides and a template is developed to summarize transcripts (32, 49). Summaries are analyzed using matrix analysis, and key actionable findings are shared with the implementation team to guide further implementation (e.g., the variable use of implementation strategies) in real time, particularly during phased implementation research such as in a hybrid type II study (20).…”
Section: Procedures For Collecting Qualitative Datamentioning
confidence: 99%
“…With a typically shorter turnaround time, qualitative researchers in implementation science have turned toward rapid analysis techniques in which key concepts are identified in advance to structure and focus the inquiry (32, 39). In the rapid analytic approach used by Hamilton (39), main topics (domains) are drawn from interview and focus group guides and a template is developed to summarize transcripts (32, 49). Summaries are analyzed using matrix analysis, and key actionable findings are shared with the implementation team to guide further implementation (e.g., the variable use of implementation strategies) in real time, particularly during phased implementation research such as in a hybrid type II study (20).…”
Section: Procedures For Collecting Qualitative Datamentioning
confidence: 99%
“…A significant proportion of veterans who receive care from the VHA are located in rural areas distant from VHA medical centers. 23 Given that communitybased clinics provide more limited mental health services, 24,25 veterans seeking specialty mental healthcare often must travel great distances to access appropriate treatment. Research has shown that greater distance from providers predicts decreased engagement in psychotherapy among veterans with a diagnosed mental health condition.…”
Section: Introductionmentioning
confidence: 99%
“…19,24 Indeed, these are among the most commonly cited reasons for not initiating treatment or for the premature discontinuation of treatment among veterans. 18,25,26 Social barriers may also impede treatment engagement, some of which may be particularly salient to individuals who have experienced a sexual trauma. For instance, veterans have described fears of being judged for seeking therapy and/or for disclosing their trauma, 14,27 as well as a fear that providers and institutions may not believe their report of experiencing MST.…”
Section: Introductionmentioning
confidence: 99%
“…Practical barriers such as inadequate transportation, shortage of local providers, and constraints due to work, school, or caregiving responsibilities are commonly cited impediments to treatment seeking both among veterans 9,12,13 and the general population. 14,15 A significant proportion of Veteran's Health Administration (VHA) users are located in rural areas distant from VHA medical centres.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 A significant proportion of Veteran's Health Administration (VHA) users are located in rural areas distant from VHA medical centres. 16 Given that community based clinics often provide more limited mental health services, 12,17 veterans seeking mental health care often must travel great distances. Research has shown distance from providers predicts decreased engagement in psychotherapy among veterans with mental health conditions.…”
Section: Introductionmentioning
confidence: 99%